A taxonomic review of the genus Junnanotrechus Uéno & Yin, 1993 (Coleoptera: Carabidae: Trechinae), with description of six new species - Belousov, Igor A.; Kabak, Ilya I. (Zootaxa, 2014)
Six new species of the genus Junnanotrechus Uéno & Yin, 1993 are described from Yunnan Province, southern China: J. wrasei sp. n. (from the Diancang Shan Mt. R.), J. triporus sp. n. (from the mountains east of Weishan), J. schuelkei sp. n. (from the Ailao Shan Mountain Range), J. elegantulus sp. n. (from the Daxueshan Mount east of Mengsa Town), J. oblongus sp. n. (from the Daxueshan Mount west of Niutoushan Village), J. koroleviellus sp. n. (from the mountains west of Yunxian Town). New taxa discovered allow a more precise definition of diagnostic characters for the genus. All species were extensively measured and morphometric indices are given. The members of the genus are keyed and their known distribution is mapped. Geographic patterns in transformations of major character states suggest the center of dispersal for members of the genus was, most likely, somewhere in the valley of the Mekong (=Lancang Jiang) River west of the Ailao Shan Mountain Range.